Performance evaluation of different transport layer protocols on the IEEE 802.11 and IEEE 802.15.4 MAC/PHY layers for WSN - Sharif, Atif; Potdar, Vidyasagar; Rathnayaka, A. (ACM Digital Library, 2009)
Wireless Sensor Networks (WSN) has gathered lot of attention from the research community lately. Among other WSN communication protocols, transport layer protocol plays a significant role in maintaining the node?s energy budget. In this context we have carried out extensive testing of various transport protocols using IEEE 802.11, IEEE 802.15.4 MAC/PHY protocol and Ad hoc On-Demand Distance Vector Routing (AODV) routing agent for WSN having multi-hop ad-hoc and WPAN network topology. The main contribution of this paper is to find out the dependency of Transport layer on MAC layer. Simulation results indicate that the underlying MAC/PHY layer protocol along with Transport layer protocol plays a vital role in achieving the high throughput, low latency and packet loss rate in WSN. For IEEE 802.11 with RTS/CTS ON high throughput, low packet drop rate and increased end-to-end packet delay is observed. While for IEEE 802.15.4 similar behavior as for IEEE 802.11 (except for UDP) but with improved power efficiency is observed. This has led the foundation for the future development of the proposed cross layered energy efficient transport protocol for multimedia application.